Efficacy of herbal dentifrice on the prevention of plaque and gingivitis as compared to conventional dentifrice: A systematic review and meta-analysis - Vini Mehta; Sahana Hegde Shetiya; Pradnya Kakodkar; Chandrashekar Janakiram; Suliankatchi Abdulkader Rizwan (Wolters Kluwer Medknow Publications, 2018)
Objective: The aim of this study was to review literature on the effects of herbal dentifrice compared to conventional dentifrice on plaque and gingival inflammation. Materials and Methods: MEDLINE, Cochrane Central Register of Controlled Trials, and major journals were explored for studies up to September 30, 2017. A comprehensive search was designed and the articles were independently screened for eligibility by two reviewers. Randomized controlled clinical trials, in which oral prophylaxis was undertaken before the intervention was introduced into the oral cavity using toothbrush were included. Where appropriate, a meta-analysis (MA) was performed and standardized mean differences (SMDs) were calculated. Results: Ten articles out of 1378 titles were found to meet the eligibility criteria. A MA showed that for plaque intervention the SMD was 2.14; 95% confidence interval (CI): 0.88-3.41, P = 0.0009; test for heterogeneity: P < 0.00001, I2 = 96% in favor of conventional dentifrice; and for gingival inflammation, the SMD was 1.37; 95% CI: 0.49-2.26, P = 0.002; test for heterogeneity: P < 0.00001, I2 = 94% which also was in favor of conventional dentifrice. Subgroup analysis for plaque intervention and gingival inflammation in case of long-term (more than 4 weeks and up to 6 months) and short-term effects (minimum of 4 weeks) of herbal dentifrice showed no difference when compared to conventional dentifrice. Conclusion: Currently, there is no high-quality evidence to support or abnegate the anti-plaque and anti-gingivitis effects of the herbal dentifrice.